UPAYA MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SISWA KELAS VII.1 TAHUN PELAJARAN 2013/2014 PADA MATERI SEL DI SMP NEGERI 1 MAJA DENGAN MENERAPKAN COOPERATIVE LEARNING TIPE TGT DAN MODEL SEL TUMBUHAN - Nurlaelati Nurlaelati (Biodidaktika : Jurnal Biologi dan Pembelajarannya, 2015)
The study aimed to analyze the enhancement of student activity and learning outcome by the implementation of cooperative learning Team Game tournament (TGT) and plant cell model from recycle materials on learning process. The research conducted on April 2014 in VII.1 class of SMP Negeri 1 Maja Kabupaten Lebak using test and non test instruments. The result showed that on two cycles of learning process, after the implementation of both modelsthere was enhancement on student activity such as discussion,asking and answering the question by the students. Learning mastery of the students also increased about 44.4%